تأثير الوعي الثقافي على اكتساب لغة ثانية: دراسة حالة لتعلم اللغة الإنجليزية بين طلاب ليبيين - Elwerfalli, Intesar (مجلة كلية الاداب, 2024)
The teaching of culture through communication has received the attention it deserves in a variety of academic and linguistic contexts across numerous institutions. To communicate in another language, a speaker must have a strong grasp of cultural norms and gestures to convey a message to someone fully. Likewise, cultural context allows for more efficient, natural communication between individuals. The aim of this study is to show Libyan instructors and learners’' knowledge about culture and language, as well as the perception toward cultural awareness as a contributing factor in learning and mastering a language. The population of this study were 20 fifth semester students of academic year 2022 and ten instructors of the Faculty of languages at the university of Benghazi. In order to achieve the goals, two questionnaires were opted as data collection tools. A questionnaire for students and another one for instructors. With regard to learners, the results of this study showed positive perception of cultural awareness as a contributing factor in learning English. Although the students knew the importance of culture, they did not link this importance to language learning. While there is a strong willingness among students to engage with cultural diversity, there is also a need for language learning curriculum to better integrate cultural content to enhance students' cross-cultural communication skills effectively. In the part of instructors, the results showed that although teachers are aware of the significance of culture and its role in mastering language learning, they do not integrate culture into their teaching in order to develop intercultural competence among learners due to some obstacles.